Historia de los pueblos de España. Tierras fronterizas (1). Andalucia y Canarias, Barcelona, 1984, Edit. Argos Vergara, 373 pp - Wagner, Carlos G. (Gerión. Revista de Historia Antigua, 1986)
Sin resumen